Optimal timing of calling in large-denomination banknotes under natural rate uncertainty - Thomas Link (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
The elimination of large-denomination banknotes is one of several options to relax the effective-lower-bound constraint on nominal interest rates. We explore timing issues associated with the calling-in of large notes from a central banker's perspective and employ an optimal stopping model to show how the volatility and the expected path of the natural rate of interest determine an optimal timing strategy. Our model shows that such a strategy can involve a wait-and-see component analogously to an optimal exercise rule for a perpetual American option. In practice, a wait-and-see component might induce a central banker not to call in large notes until the natural rate has fallen to an exceptionally low level.
Keywords: E42; E58; 330; cashless economy; phase-out of paper currency; wait-and-see policy; optionvalue